Balance of the Circulation Materials and Behavior of the Various Components in the Lead Smelting Process at Chigirishima Refinery - Koichi Yamazaki; Toshio Kurikami (The Minerals, Metals and Materials Society, 2000)
"Toho Zinc Co., Ltd Chigirishima Refinery has the production capacity of electrolytic lead for 95000t/y by sintering- blast furnace electrolytic process. Lead raw materials are lead concentrates, spent batteries and dusts that contain lead from other companies, and these are handled by existing smelting process. There are many circulation materials in the process, because the system has been constructed with improving the recovery rate and protecting the environment. This report describes material balance in each process, distribution of the lead and various components, and it examines present state of the processing. In addition, we report the result that we have tried to improve the work environment.IntroductionThe Chigirishima Refinery of the Toho Zinc Co., Ltd. is located in Chigirishima, an island 4km off the coast of Takehara-city, Hiroshima, Japan. The Chigirishima Refinery began lead smelting operations in 1951.The Chigirishima Refinery adopted the sintering-blast furnace-electrolytic process and has an electrolytic lead production capacity of 95,000 tons/year. The existing smelting process handles raw materials from lead concentrates, spent batteries, and lead-bearing dust from other companies. This system was constructed with the intentions of improving material recovery ratios and protecting the environment; therefore, there are many materials recirculating throughout the smelting process. This report describes the material balance in each process and the distribution ciflead and various components, and it examines the present state of processing. In addition, we report the results of our attempts to improve the work environment."